2018
DOI: 10.5812/ijpbs.12759
|View full text |Cite
|
Sign up to set email alerts
|

Shared PTSD and Paradox Insomnia Among Wives of Veterans with Chronic War Induced PTSD: A Preliminary Study

Abstract: Background: War-induced Post-Traumatic Stress Disorder (PTSD) and its complications can be passed on to patients' family members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Many studies assessed factors that predict the level of PTSD symptoms or presence of probable PTSD among family members. Higher levels of PTSD symptoms or presence of probable PTSD among informal supporters in military samples appeared to be significantly and positively associated with partner’s suicidal ideation (Zerach et al, 2016), presence of PTSD or PTSD severity in survivor (Ahmadi et al, 201; Bramsen et al, 2002; Dekel et al, 2016, 2018; Dirkzwager et al, 2005; Greene et al, 2014; Koić et al, 2002; Mohammadi et al, 2018), duration of survivor’s symptoms (Ahmadi et al, 2011), degree of exposure to survivor physical aggression (Dekel & Solomon, 2006), level of affective empathy (Dekel et al, 2018), partner’s own trauma history (Al-Turkait & Ohaeri, 2008; Dekel et al, 2018), partner’s fusion with the survivor (Dekel, 2010; Lahav et al, 2017), partner’s anxious and avoidant attachment (Ein-Dor et al, 2010; Lahav et al, 2016), partner's feelings of ambiguous loss (Dekel et al, 2016), and length of marriage (Frančišković et al, 2007). Only two studies of military couples found that veterans’ trauma history was not associated with partner’s PTSD symptom levels (Wolf et al, 2013) or presence of probable PTSD in partners (Al-Turkait & Ohaeri, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies assessed factors that predict the level of PTSD symptoms or presence of probable PTSD among family members. Higher levels of PTSD symptoms or presence of probable PTSD among informal supporters in military samples appeared to be significantly and positively associated with partner’s suicidal ideation (Zerach et al, 2016), presence of PTSD or PTSD severity in survivor (Ahmadi et al, 201; Bramsen et al, 2002; Dekel et al, 2016, 2018; Dirkzwager et al, 2005; Greene et al, 2014; Koić et al, 2002; Mohammadi et al, 2018), duration of survivor’s symptoms (Ahmadi et al, 2011), degree of exposure to survivor physical aggression (Dekel & Solomon, 2006), level of affective empathy (Dekel et al, 2018), partner’s own trauma history (Al-Turkait & Ohaeri, 2008; Dekel et al, 2018), partner’s fusion with the survivor (Dekel, 2010; Lahav et al, 2017), partner’s anxious and avoidant attachment (Ein-Dor et al, 2010; Lahav et al, 2016), partner's feelings of ambiguous loss (Dekel et al, 2016), and length of marriage (Frančišković et al, 2007). Only two studies of military couples found that veterans’ trauma history was not associated with partner’s PTSD symptom levels (Wolf et al, 2013) or presence of probable PTSD in partners (Al-Turkait & Ohaeri, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies identified physical health concerns among supporters of trauma survivors including fatigue (Macdonell et al, 2010; Mansfiled et al, 2014; Outram et al, 2009); sleep quality (Akoondzadeh et al, 2017, 2018; Dirkzwager et al, 2005; Ferrell et al, 2019; Gregory et al, 2017; MacDonnell et al, 2010; Mohammadi et al, 2018; Outram et al, 2009); weight changes and appetite loss (Ferrell et al, 2019; Gregory et al, 2017); somatic concerns such as stomach aches, chest pains, headaches, and migraines (Dirzwager et al, 2005; Ferrell et al, 2019; Glass et al, 2012; Gregory et al, 2017; Koić et al, 2002; Mikulincer et al, 1995; Solomon et al, 1992; Westerink & Giarratano, 1999); and more specific health problems such as cardiovascular disease and gastrointestinal problems (Klarić et al, 2012; Outram et al, 2009). Among a sample of military partners, partners’ higher reports of their partners’ PTSD symptoms significantly predicted higher reports of own somatic concerns (Solomon et al, 1992).…”
Section: Resultsmentioning
confidence: 99%